IMPLEMENTATION OF TRANSMITTER LEVEL CONTROL SYSTEM ON FA-150 TANK - puan natalia sirait (Universitas PGRI Palembang, 2022)
Instrumentation is a very important tool in measuring systems, one of which is to measure the height of the liquid level. This tool must be able to function properly according to the instrumentation requirements of the factory. This instrumentation tool is one of the determinants of production results, and the instrumentation tool measures, controls, recognizes and analyzes both manually and automatically. PT Sintas Kurama Perdana decides and sets the company's Vision and Mission as follows: Where the Range value must be in the range of 0% - 100%, input 4-20 mA, pressure input is the resulting pressure (incH20), the lowest input range is 0, the input span is in the transmitter work area, the output span must be 100% pressure generated (incH20), the lowest output range is 4 mA. control system on the FA-150 at PT. From Kurama Perdana, several conclusions can be drawn, namely the control system or control system is a system consisting of several system elements that have the aim of regulating or controlling a process to obtain a desired amount. The level transmitter on the FA-150 tank used at PT. Syntas Kurama Perdana uses a closed loop system that relies on feedback.Keywords : Transmitter, Control, Tanki, Tekanan.